Assessing the Dynamics of Agricultural Growth and Its Socio-Economic Effects: A Case Study of Hisar District (Leadership, Education, Personality: An Interdisciplinary Journal, ISSN: 2524-6178, 2025)
This study examines the impact of technological advancements on agricultural productivity, focusing on both the socio-economic benefits and challenges associated with agricultural growth. Utilizing data from academic journals, government reports, and industry analyses, the research highlights significant gains in productivity through innovations such as precision agriculture, drones, and automated machinery. Findings reveal a 50% increase in average farmer income and a 10% rise in employment rates, alongside notable improvements in rural infrastructure and food security. However, the study also identifies critical challenges, including environmental degradation, rising income inequality, and displacement of communities. The analysis integrates quantitative data from surveys and statistical databases with qualitative insights from field studies, providing a comprehensive view of how technological advancements shape agricultural development and its broader socio-economic impacts.